The Development of English Writing Learning Material through a Genre Based Approach for English Department at University - I Wy. Dirgayasa (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
Generally, this research attempts to find out the relavant English writing learning materials in order to develop a genre-based writing course for college students at English Department at university. Particularly, its objectives are 1) to know the existing phenomena of teaching and learning writing process, 2) to find out the relevant English writing learning materials,3) and to develop a genre-based writing course.The research is done by applying research dan development (R&D) method. The respondents of this research are active students, alumni, and lecturers, The data are collected by documentary sheet, questionaire, and in depth in interview. The data are analyzed by descriptive analysis. The results of the research show that 1) in general the process of teaching and learning of genre based writing is not optimally yet such as the teaching strategies used by lecturers, unadequate  and less relevant writing materials, and assessment method, 2) the genre writing learning materials are classified into two categories-short functional texts and long functional texts, and 3) the physical structure of a genre-based writing course consists of two parts-preliminary and main parts. The preliminary has preview and the main part consists of  1) Getting Started, 2) The Orientation dan elaboration,  3) Teaching and learning strategy, 4) following up,  and 5) Assessment